L’industrie, la ville, la palmeraie au désert. Un quart de siècle d’évolution au Sahara algérien - Bisson, Jean (Maghreb-Machrek, 1983)
Bilan partiel des transformations du Sahara algérien depuis les années 60, axé principalement sur les modifications de l’organisation de l’espace et les différentes formes que revêt l’intégration à l’échelle nationale. Trois aspects sont successivement analysés : le rôle du chantier dans la structuration régionale du Nord-Est saharien (wilayate de Ouargla et Laghouat), l’évolution du nomadisme (wilaya de Ouargla) et la place des paysanneries (principalement celles du Centre-Ouest : wilaya d’Adrar), la ville en tant que révélateur du rôle nouveau qui lui est dévolu et de l’identité régionale qu’elle résume (avec trois exemples : Ouargla, Beni Sguen (Mzab), Timimoun (Gourara).
Keywords: Urbanisme -- Mzab

Les villes sahariennes. Politique volontariste et particularismes régionaux - Bisson, Jean (Maghreb-Machrek, 1983)
Après avoir établi un bilan des modifications de l’organisation spatiale du Sahara algérien (formation de bassins d’emplois industriels, survivance de l’élevage nomade, adaptation des petites paysanneries), ce second article, qui constitue le troisième volet de l’étude, met l’accent sur l’authenticité de la ville saharienne. Trois villes (Ouargla, Beni Sguen, Timimoun) ont été choisies parce que, malgré l’uniformisation des modes de vie et la standardisation des programmes d’urbanisme, elles restent très représentatives de la diversité régionale saharienne ; chacune traduit cependant les facettes multiples d’une intégration poussée à l’Algérie nouvelle.
Keywords: Urbanisme -- Mzab

La cité ibadite: urbanisme et vie sociale au XIe siècle d'après un document inédit : d'Abū 'l-Abbas Ahmad, le Kitab Uṣūl al-Araḍīn - Cuperly, Pierre (Compte-rendu de la Réunion des chercheurs sur le monde arabe et musulman, Aix-en-Provence, 30 juin, 1er & 2 juillet 1986, 1986)
Keywords: Urbanisme -- Mzab

Cities in the Sahara: Spatial Structure and Generative Processes - Salah-Salah, Fatiha (University College, 1987)
p. 65-114 : Ghardaïa et Beni Isguen p. 124-145 : The Social use of space in the Mzab Towns and Ghadames P. 199-246 : Spatial description of the Towns' Fabric of Ghardaia and Beni Isguen
Keywords: Urbanisme -- Mzab

Communities in Transition, Five Urban Jewish Communities and their Architecture - Gitai, Amos (University of California, 1986)
Chapter 4 : The jewish quarter of Ghardaia
Keywords: Judaïsme -- Mzab; Urbanisme -- Mzab

La cité ibadite: urbanisme et vie sociale au XIe siècle d'après un document inédit : le Kitab Talkhīṣ al-Qisma et le Kitab Uṣūl al-Araḍīn d'Abū 'l-Abbas Ahmad - Cuperly, Pierre (Awal. Cahiers d'études berbères, 1987)
Keywords: Urbanisme -- Mzab

La cité ibadite: urbanisme et vie sociale au XIe siècle (suite et fin) - Cuperly, Pierre (Awal. Cahiers d'études berbères, 1988)
Keywords: Urbanisme -- Mzab

La vallée du M'Zab : urbanisme et perspectives de développement (Colloque régional sur la gestion des grandes villes d'Algérie, 1988)
Keywords: Urbanisme -- Mzab

M'zab community, Algeria, North Africa: Its planning and architectural aspects--past, present, and future - Solieman, Khalifa Ali (University of Arizona, 1988)
This thesis is a report of a study of some aspects of the architecture and urban planning of the M'zab Valley communities of southern Algeria, North Africa. The interrelation of physical planning and religious/social structures of the communities of the M'zab Valley are explored. This study was concerned with the following questions: (1) What are the various environmental factors that influence the design values of the M'zabites? (2) To what extent is the distinctive style of architecture in the M'zab due to religion: the Ibadi heritage or Islam in general? (3) How has the M'zab social structure responded to outside influences in recent years? (4) What is the present trend of the M'zab urban communities in architecture and planning?
Keywords: Architecture -- Mzab; Urbanisme -- Mzab

Quelques remarques sur l’activite des Roustemides au Maghreb Central dans le domaine de l’urbanisme - Dąbrowski, Leszek M. (Rocznik Orientalistyczny, 1985)
Keywords: Urbanisme -- Mzab

Un document ancien sur l’urbanisme au Mzab - Cuperly, Pierre (Revue de l'Institut des Belles Lettres Arabes, 1981)
Arabic text and translation of the last chapter (112-118) of the third part of Kitāb Uṣūl al-Arāḍīn by Abū ‘l-ʿAbbās Aḥmad b. Abī ʿAbdl. Muḥ. b. Abī Bakr [al-Nafūsī]. Mainly on irrigation.
Keywords: Urbanisme -- Mzab

Cultural ecological theory and the formation of the Ibadite desert confederacy - Bennoune, Mahfoud (Dialectical Anthropology, 1986)
Keywords: Urbanisme -- Mzab

L'habitat mozabite au M'zab - Bousquet, Christian (Annuaire de l'Afrique du Nord, 1986)
Keywords: Urbanisme -- Mzab

Pérennité du centre ancien au M'zab : le cas de Beni-Isguen - Bousquet, Christian (Urbama, 1982)
Keywords: Urbanisme -- Mzab

Les nouveaux citadins de Beni Isguen au M'zab (Sahara algérien) - Bousquet, Christian (Urbama, 1986)
Keywords: Urbanisme -- Mzab

Le M'zab, espace et société - Benyoucef, Brahim (Acta Geographica, 1981)
Keywords: Urbanisme -- Mzab

Towards a socio-cultural approch for the design of the house settlement system : a case study in Ghardaia, Algeria - Chabbi, Naima (University of Newcastle Upon Tyne, 1988)
Rapid urbanisation which is a characteristic of most developing countries, has led to the importation of readily available solutions and to an overgeneralisation of human needs. The main objective of this study is to relate design to man's social and cultural needs. First, the study demonstrates the relationship between cultural and social variables that influence house form and settlement patterns. This is followed by a comparative case study analysis of existing house-settlement systems in two residential areas; one a modern government built scheme, the other a traditional development, both in the M'Zab, in Southern Algeria. The main assumption was that traditional houses and settlements were culturally more responsive than their modern equivalents. However, results refuted this assumption and indicated that social change affected many of people's values and attitudes towards housing. This indicates that neither international modernism, in housing provision, nor an attempt to slavishly copy past indigenous solutions are likely to be successful. Through studying human-environmental behaviour and using multiple-methods strategies, it is possible to bridge the gap between design and social research. A reorientation of the educational system would help towards a better communication not only between different professional practices and disciplines, but also involving the lay people. Finally, this study suggests that designing for potential adaptability a characteristic of traditional design, reflects culture, and would not only accommodate change, but would also involve active participation by people and therefore raise the level of responsibilty and satisfaction. The research combined evidence from documentary sources and field surveys. A multiple-method strategy was adopted to compare the two settlement systems of the case study. This included direct observation, interviews and trade-off games. The interview survey included three groups of people: the users, the local planning authorities and the building contractors. By stressing the socio-cultural variables, this study does not deny the role of other variables. On the contrary, the author accepts that design activities should aim towards maintaining a balance between environmental factors and financial constraints. It is, however, argued that human needs must be given at least the same degree of importance, if workable solutions to the problem of rapid urbanisation are to be found.
Keywords: Urbanisme -- Mzab

Effects of privacy on the built form and the social construction in Ghardaïa, Algéria - Laroui, Mohamed (University of Nottingham, 1987)
Keywords: Urbanisme -- Mzab

Le Processus d'urbanisation et les transformations sociales au M'Zab (Algérie) - Benyoucef, Brahim (Université de Paris 4, 1983)
Keywords: Urbanisme -- Mzab

Mutations urbaines en Algérie: le cas de Beni Isguen au M'Zab - Bousquet, Christian (Université François Rabelais, 1983)
Keywords: Urbanisme -- Mzab

Le M'Zab, les pratiques de l'espace - Benyoucef, Brahim (Entreprise nationale du livre, 1986)
Keywords: Urbanisme -- Mzab